2023
DOI: 10.1136/bmjopen-2023-077702
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting point-of-care ultrasound implementation in general practice: a survey in Danish primary care clinics

Camilla Aakjær Andersen,
John Brandt Brodersen,
Ole Graumann
et al.

Abstract: ObjectiveThe implementation of point-of-care ultrasound (POCUS) in general practice varies, but it is unknown what determines this variation. The purpose of this study was to explore (1) the overall proportion of POCUS-users among general practitioners (GPs), (2) the current use of POCUS by GPs, (3) factors related to the implementation of POCUS in general practice and (4) GPs’ concerns related to POCUS use in general practice.DesignAn online survey was distributed in June 2019.SettingGeneral practice.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Point-of-care Ultrasound (POCUS) is an effective bedside diagnostic tool that has been shown to improve patient outcomes in recent years [ 1 ]. As more physicians learn about POCUS, its usage continues to expand across nearly all clinical specialties and settings, including acute care hospitals, primary care clinics, and resource-limited and rural settings [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point-of-care Ultrasound (POCUS) is an effective bedside diagnostic tool that has been shown to improve patient outcomes in recent years [ 1 ]. As more physicians learn about POCUS, its usage continues to expand across nearly all clinical specialties and settings, including acute care hospitals, primary care clinics, and resource-limited and rural settings [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential advantages, widespread adoption of POCUS use has been slow, with reports suggesting that only about 10% of general physicians use POCUS [ 4 ]. Several studies have revealed important barriers to POCUS use [ 3 , 5 9 ].…”
Section: Introductionmentioning
confidence: 99%